AUDIT TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN KERANGKA KERJA CONTROL OBJECTIVE FOR INFORMATION AND RELATED TECHNOLOGY (COBIT) VERSI 4.1 PADA DOMAIN ACQUIRE AND IMPLEMENT (STUDI KASUS: INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE) - Abigail Angelica; Budi Wasito (Jurnal Informatika dan Bisnis, 2020)
Institut Bisnis dan Informatika Kwik Kian Gie has the main goal of "being one of the leading schools of business in Indonesia with regional and international insight with superior quality based on world-class university standards". One of the criteria to become a world-class university standard is to apply good IT governance to institutions. Therefore, it is necessary to hold a process of assessing the level of maturity of the information technology governance process, especially in the process that is being carried out. The measurement of the level of maturity is carried out using the Control Objective for Information and Related Technology (COBIT) version 4.1 framework in the Acquire and Implement domain by comparing the findings with the standard maturity level of COBIT. The results of this level of maturity assessment are the level of maturity at Institut Bisnis dan Informatika Kwik Kian Gie is still at level two or repeatable but intuitive. Therefore, there needs to be an improvement to increase the level of maturity to reach the criteria of a world-class university.